Report of the Road Transport Road Transport Reorganisation Committee 1959 - Planning Commission (Planning Commission, 1959)
The proposal to set up a Committee to advise on the reorganisation of the transport administration in the States was first mooted at the State Transport Commissioners/Controllers Conference in August, 1955, and accepted by the Transport Advisory Council in February, 1956. the proposal was also discussed by the Transport Commissioners/Controllers Conference in October 1957. In accordance with the recommendations of the Transport Advisory Council, the Government of India on May 5, 1958, appointed this Committee to conduct a comprehensive enquiry and make recommendations for the reorganisation of the transport administration in the States and other cognate matters.
Ministry of Transport & Communications